Evaluation of the auditory system in autistic children using evoked otoacoustic emissions and a contralateral suppression test - OYSU, ÇAĞATAY (My University, 2022)
In this study, we evaluated the cochlea, medial olivocochlear system, and brainstem function in autistic children using evoked otoacoustic emissions (OAEs) and a noninvasive contralateral suppression (CLS) test. In total, we included 21 autistic children with normal hearing (study group) and 11 healthy children (control group). Transient-evoked OAEs (TEOAEs) and CLS of TEOAE were evaluated in the left and right ears of all patients. In a silent room, spontaneous, transient, and dP ILO292 were evaluated. The mean age of the study and control group was 9.1 years (range: 6-13 and 6-12 years, respectively). For the study group, there was no statistically significant difference between the OAE and CLS values of the right ear (P > .05). However, for the left ears, OAE values were statistically significantly higher than the CLS values (P < .05). In the control group, the OAE values of both ears were statistically significantly higher than the CLS values (P < .05). In autistic children with normal hearing, the medial olivocochlear system functions more effectively in the right ear than the left ear. Asymmetry between the ears is likely responsible for the peripheral auditory lateralization and independence in auditory function between the left and right ears.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Medicine; Health Sciences; Surgery Medicine Sciences; Otolaryngology; KULAK BURUN BOĞAZ; Klinik Tıp; Klinik Tıp (MED); OTORHINOLARYNGOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Konuşma ve İşitme; Otorhinolaryngology; Speech and Hearing; auditory system; autism; evoked otoacoustic emissions; contralateral suppression; STIMULATION; ASYMMETRY; RESPONSES; auditory system; autism; evoked otoacoustic emissions; contralateral suppression